Dynamic Properties of Pot Bearing Via Modal Analysis - Yusuf, Ahmad Idzwan; Mohd Amin, Norliyati; Yunus, Mohd Azmi; Yahya, Norrul Azmi (International Journal of Integrated Engineering, 2025)
Bearings represent one of the most sensitive and demanding elements in load transfer, particularly in structural support systems, which have some of the highest requirements regarding reliability and performance in structural engineering. One widely used structural bearing is the mechanical pot bearing. This compact bearing is especially useful for transmitting large vertical loads while accommodating extensive movements and multi-directional rotation. Understanding the dynamic behavior of the pot bearing in terms of natural frequencies, mode shapes, and damping is a necessity for enhancing its design and failure limit. Since it is composed of several materials, the pot bearing exhibits complex material behavior, making the measurement of its dynamic properties challenging in real practice. Modal analysis is one of the best methods used to determine the dynamic properties of materials. Consequently, the main objective of this research is to determine the dynamic properties of the pot bearing, specifically natural frequencies, mode shapes, and damping, through numerical modeling and experimental work based on modal analysis. From the findings, the relative errors between the finite element and experimental modal analyses for the first mode are quantified at 15.29%, whereas for the second mode, the corresponding value is 10.13%. The third mode demonstrates a relative error of 9.67%, while the fourth mode exhibits the lowest relative error of 8.81%. A strong agreement in mode shape was observed between the finite element model and experimental modal analysis results. In conclusion, modal analysis proved to be an effective technique for capturing the dynamic characteristics of pot bearings. The validated numerical model offers a reliable basis for further analysis, optimization, and integration into broader structural dynamic assessments.